Comparison of ploughing vs. ploughless cultivation in terms of energy expenditure and quality - Szczyglak, Piotr (Technical Sciences, 2021)
The article discusses the basic technologies of soil cultivation and presents the results of analyses of the effectiveness of the product resource base of ploughless cultivation machines manufactured in Poland. The study also describes the design of a prototype MultiCat 6HD aggregated tillage unit, which should be regarded as innovative, and presents the methodology of experimental research focused on the aggregated unit and machines for traditional plough tillage. The experiment determined fuel consumption, effective and operational efficiency, the depth of placing and mixing of crop residues and the indicator of crop residue surface embedding. Based on the conducted analyses, it was found that ploughless cultivation required approx. 30% less expenditure for fuel as compared to the traditional plough tillage. In addition, a more favourable distribution of plant material within the soil profile was found along with almost identical embedding of crop residues, as compared to the plough tillage. It was demonstrated that the application of ploughless cultivation based on the MultiCat 6HD aggregated unit would improve agricultural farm competitiveness.